Akibat Hukum Pengusaha Melakukan Perbuatan Curang pada Masa Pandemi Dikaitkan dengan Perundang-Undangan Yang Berlaku - Abraham Radja; Imam Haryanto (Universitas Batanghari Jambi, 2021)
This writing is written to find out the fraudulent acts committed by business actors during the pandemic and how the legal consequences arise from these fraudulent acts. This research is a juridical normative type with a statutory approach using secondary data collected through literature study. From this writing, it can be concluded that dominant position, Price fixing, and hoarding are a form of fraudulent and interrelated acts committed by business actors in the current pandemic era. Administrative sanctions, fines, imprisonment or additional penalties are given to comply with the applicable provisions for parties who commit several forms of fraud during the pandemic period.